Agrobiological Evaluation of Varieties and Methods Used in Growing Garlic in the Forest-Steppe Zone (in the Republic of Ingushetia) - Galaev , Batyr; Bazgiev, Magomed; Kostoyeva, Liza; Gutseriev, Israil (KnE Life Sciences, 2021)
Increasing the production and quality of garlic yield is an important agricultural challenge. In the varying agro-ecological conditions of the North Caucuses, the yield of this crop largely depends on the planting technology and the level of its intensity. Important factors that determine the quality of the garlic yield are the use of varieties adapted to these agro-climatic conditions, high-quality planting materials and agricultural technology that meets the requirements of the crop, and the agro-climatic conditions of the region. At present, the potential productivity of varieties used in the Republic is only 30-40 percent. This is due to the insufficient development of planting technologies that take into account the specific ecological conditions of the region. This study examines the factors regulating the yield and quality of garlic varieties. Keywords: garlic, fertilizers, planting schemes, variety, planting material, vegetation